A new p-dimethylaminocinnamaldehyde reagent formulation for the photoluminescence detection of latent fingermarks on paper. (December 2015) - Fritz, Patrick; van Bronswijk, Wilhelm; Lewis, Simon W.
Graphical abstract: Highlights: p-Dimethylaminocinnamaldehyde (DMAC) re-evaluated for the detection of latent fingermarks. New formulation reliably develops latent fingermarks on paper surfaces. Successful application to thermal paper without modification of formulation. Able to detect fingermarks on paper at least 6 months after deposition. Abstract: Dimethylaminocinnamaldehyde was re-evaluated as a wet contact reagent for the treatment of latent fingermarks on porous substrates. A new formulation (consisting of 0.028 g p-dimethylaminocinnamaldehyde, 0.84 mL glacial acetic acid, 6.2 mL ethyl acetate and 0.993 L 40–60 °C petroleum spirits) provides quick, sensitive and robust luminescent ridge detail within 3 h of treatment on both plain and thermal paper. Comparisons to existing formulations indicate improved visualisation and/or a more efficient process.